Role of autophagy in hypoxia-reoxygenation-induced injury of rat alveolar epithelial cell type Ⅱ - LIU Xiu-jie, WANG Xin-yun, SONG Zheng-yang, LOU Guo-qiang, HAO Mao-lin, QIAN Wei, WANG Wan-tie (Jichu yixue yu linchuang, 2021)
Objective To investigate the role of autophagy in the hypoxia-reoxygenation (H/R) model of rat alveolar epithelial cell type Ⅱ (AEC Ⅱ). Methods Cells were randomly divided into control group (C),hypoxia-reoxygenation group (H/R),solvent group (HD),autophagy agonist group(Rap) and autophagy inhibitor group (3-MA).Pretreated cells with 3-mA 1h before hypoxia. The cell viability was determined with CCK-8, and used RT-PCR, Western blot to detect the expression of autophagy related mRNA transmission and its proteins, and ultrastructure of cell was examined by electron microscopy. Results Compared to the C group, the cell viability decreased, the expression of autophagy related proteins and gene transcription increased, and the cell ultra-structure was significantly damaged (P＜0.05). The cell viability in 3-MA group was higher than that of H/R group, the autophagy related proteins and their gene transcription were all decreased (P＜0.05), the cell structure was damaged slightly,and autophagy body was not found. Conclusions Hypoxia-reoxygenation can activate autophagy and induce alveolar epithelial cell type Ⅱ damage.